1997
DOI: 10.1148/radiology.203.2.9114104
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma in patients who undergo liver transplantation: sensitivity of CT with iodized oil.

Abstract: CT with iodized oil failed to provide any substantial information in the pre-OLT staging of HCC: It was inaccurate for small HCC nodules (<2 cm) and intrahepatic metastases. Its sensitivity matched that of digital subtraction angiography and was statistically significantly inferior to that of CTAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 0 publications
1
23
0
2
Order By: Relevance
“…First, there is a general trend toward reduced detection ability with both imaging techniques as the tumors become smaller and more differentiated. This observation is in line with that reported by Spreafico et al 31 for Lipiodol CT and by Ohashi et al 37 for dynamic incremental CT. Nonetheless, the sensitivity of helical CT for well-differentiated HCC is superior to that of Lipiodol CT or DSA, especially when tumors are small, whereas Lipiodol CT shows sensitivity superior to that of helical CT in detecting small but moderately to poorly differentiated HCCs.…”
Section: Discussionsupporting
confidence: 93%
“…First, there is a general trend toward reduced detection ability with both imaging techniques as the tumors become smaller and more differentiated. This observation is in line with that reported by Spreafico et al 31 for Lipiodol CT and by Ohashi et al 37 for dynamic incremental CT. Nonetheless, the sensitivity of helical CT for well-differentiated HCC is superior to that of Lipiodol CT or DSA, especially when tumors are small, whereas Lipiodol CT shows sensitivity superior to that of helical CT in detecting small but moderately to poorly differentiated HCCs.…”
Section: Discussionsupporting
confidence: 93%
“…Comparing the results of imaging modalities with the histopathologic data provides a clearly more precise assessment of the value of these methods than the usually performed comparison of radiologic modalities with a gold standard or the pathologic assessment of only a part of the liver after partial hepatic resection. 20 -24 Recently some authors have reported tumor detection rates of 37% to 71% by multiphasic HCT in transplant patients, 7,20 -23 a sensitivity of 58% for CT with iodized oil 24,27 and a sensitivity of 85% for CT during arterial portography. 24 Krinksy et al 28 observed disappointing results of gadolinium-enhanced magnetic resonance imaging compared with pathologic examination of explanted livers (HCC tumor detection rate 55%).…”
Section: Discussionmentioning
confidence: 99%
“…7 Lipiodol CT has a greater accuracy for tumor identification than either CT or angiography alone. 8,9 Unfortunately, none of the imaging modalities is perfect, and even with multiple investigations, comparison of the imaging studies with pathological tumor assessment after removal shows that tumors are understaged preoperatively in 25% or more of the cases. 10 Therefore, it is not uncommon for surgery to be performed for lesions that ultimately prove to be more extensive than indicated by preoperative investigations.…”
Section: Hcc With Cirrhosismentioning
confidence: 99%